Electrolyte and lithium ion battery
By using electrolyte with nonaqueous organic solvents and specific additives in lithium-ion batteries, the degree of infiltration of electrolytes is improved and the SEI film is formed, which solves the problem of insufficient infiltration of electrolytes under liquid-poor conditions and improves the fast charging of lithium-ion batteries , cycle and high temperature performance.
Patent Information
- Application Number
- CN202411682186.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-01-17
AI Technical Summary
The electrolyte infiltrates in existing lithium-ion batteries under liquid lean conditions, which affects its fast charging performance, cycle performance and high temperature resistance.
Using an electrolyte solution, including nonaqueous organic solvents, lithium salts and specific additives, the first additive and the second additive, the wetting degree of the electrolyte solution is improved through synergistic action, forming a dense and uniform solid electrolyte phase interface (SEI film) to optimize Lithium ions migration and charge transfer reduce impedance.
It significantly improves the fast charging performance, cycle performance and high temperature resistance of lithium-ion batteries under liquid lean conditions, and enhances the stability and high temperature storage performance of the battery.
Smart Images

Figure CN119324256A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to an electrolyte and a lithium-ion battery. Background Art
[0002] With the rapid development of new energy technologies, lithium-ion batteries are increasingly used in 3C digital devices, electric bicycles, electric vehicles, power tools and other fields. At this stage, the performance and safety requirements for lithium-ion batteries are becoming increasingly higher. However, the energy density, fast charging performance and safety performance of existing lithium-ion batteries are difficult to meet people's needs, especially the slow charging speed and insufficient safety.
[0003] In lithium-ion batteries, non-aqueous electrolyte is an important factor affecting the performance of lithium-ion batteries. During the charge and discharge process of lithium-ion batteries, the electrolyte reacts electrochemically with the positive and negative electrodes to form a passivation film. The passivation film can prevent the further decomposition of the electrolyte and plays a decisive role in the charge and discharge performance of lithium-ion batteries. Although setting a lean liquid condition can increase the energy density of lithium-ion batteries, the degree of electrolyte wetting on the electrode and diaphragm under lean liquid conditions is greatly reduced, thereby affecting the cycle stability of lithium-ion batteries. Therefore, how to improve the degree of electrolyte wetting on the electrode and diaphragm under lean liquid conditions, thereby improving the fast charging performance, cycle performance, and high temperature resistance of lithium-ion batteries, has become one of the difficulties and bottlenecks in the design of lithium-ion batteries. Summary of the invention
[0004] The purpose of this application is to provide an electrolyte and a lithium-ion battery to improve the infiltration degree of the electrolyte under lean conditions, thereby improving the fast charging performance, cycle performance and high temperature resistance of the lithium-ion battery. The specific technical solution is as follows: The first aspect of the present application provides an electrolyte, which includes a non-aqueous organic solvent, a lithium salt and an additive; the additive includes a first additive and a second additive, the first additive includes a compound shown in Formula 1, and the second additive includes a compound shown in Formula 2: ;
[0005] wherein R1 and R2 are each independently selected from hydrogen, unsubstituted or replaced by R a Replaced , unsubstituted or replaced by R a Replaced , unsubstituted or replaced by R a Replaced , and R1 and R2 are not hydrogen at the same time; R a Selected from , or ; R3, R4 and R5 are each independently selected from carbon, oxygen, or , and at least one of R3, R4 and R5 is selected from or , at least one of R3, R4 and R5 is selected from oxygen atoms; and the compound represented by formula 1 contains at least one and a ; R6-R 11 are independently selected from hydrogen, halogen, phenyl, hydroxyl, C1-C6 hydrocarbon group, C1-C6 halogenated hydrocarbon group, and R6-R 11 Not at the same time hydrogen; Based on the total mass of the electrolyte, the mass percentage of the first additive is P1, the mass percentage of the second additive is P2, 0.1%≤P1≤10%, 0.05%≤P2≤5%.
[0006] In some embodiments of the present application, 0.25%≤P1≤2%, 0.1%≤P2≤1.5%.
[0007] In some embodiments of the present application, the first additive is selected from at least one of the compounds represented by Formula 1-1 to Formula 1-4: .
[0008] In some embodiments of the present application, the second additive is selected from at least one of the compounds represented by Formula 2-1 to Formula 2-13: .
[0009] In some embodiments of the present application, the additive includes a third additive, and the third additive is selected from at least one of vinylene carbonate, fluoroethylene carbonate, ethylene sulfate, 1,3-propane sultone, vinyl sulfite and lithium difluorobis(oxalate)phosphate; based on the total mass of the electrolyte, the mass percentage of the third additive is P3, 0.5%≤P3≤5%, preferably, 1%≤P3≤2%.
[0010] In some embodiments of the present application, the third additive is selected from vinylene carbonate (VC) and 1,3-propane sultone (PS); the mass ratio of vinylene carbonate to 1,3-propane sultone is (0.25~4):1.
[0011] The second aspect of the present application provides a lithium ion battery, which includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet includes a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode material layer includes a positive electrode active material; based on the total mass of the positive electrode material layer, the mass percentage of the positive electrode active material is C p , the filling coefficient of lithium-ion battery is I c g / Ah, lithium-ion batteries meet: .
[0012] In some embodiments of the present application, 2.2≤I c ≤3.5, 92%≤C p ≤98%.
[0013] In some embodiments of the present application, .
[0014] In some embodiments of the present application, 2.7≤I c ≤3, 94%≤C p ≤97%.
[0015] Beneficial effects of this application: The present application provides an electrolyte, which includes a non-aqueous organic solvent, a lithium salt and an additive; the additive includes a first additive and a second additive, the first additive includes a compound shown in Formula 1, and the second additive includes a compound shown in Formula 2; based on the total mass of the electrolyte, the mass percentage of the first additive is P1, the mass percentage of the second additive is P2, 0.1%≤P1≤10%, 0.05%≤P2≤5%. Through the synergistic effect of the first additive and the second additive, the electrolyte infiltration degree under lean liquid conditions can be improved, thereby improving the fast charging performance, cycle performance and high temperature resistance of the lithium-ion battery.
[0016] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. DETAILED DESCRIPTION
[0017] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.
[0018] The first aspect of the present application provides an electrolyte, which includes a non-aqueous organic solvent, a lithium salt and an additive; the additive includes a first additive and a second additive, the first additive includes a compound shown in Formula 1, and the second additive includes a compound shown in Formula 2: ; wherein R1 and R2 are each independently selected from hydrogen, unsubstituted or replaced by R a Replaced , unsubstituted or replaced by R a Replaced , unsubstituted or replaced by R a Replaced , and R1 and R2 are not hydrogen at the same time; R a Selected from , or ; R3, R4 and R5 are each independently selected from carbon, oxygen, or , and at least one of R3, R4 and R5 is selected from or , at least one of R3, R4 and R5 is selected from oxygen atoms; and the compound represented by formula 1 contains at least one and a ; R6-R 11 are independently selected from hydrogen, halogen, phenyl, hydroxyl, C1-C6 hydrocarbon group, C1-C6 halogenated hydrocarbon group, and R6-R 11 Not at the same time hydrogen; Based on the total mass of the electrolyte, the mass percentage of the first additive is P1, and the mass percentage of the second additive is P2, 0.1%≤P1≤10%, 0.05%≤P2≤5%; preferably 0.25%≤P1≤2%, 0.1%≤P2≤1.5%. For example, P1 can be 0.1%, 0.2%, 0.25%, 0.5%, 0.8%, 1%, 1.5%, 2%, 3%, 5%, 7%, 9%, 10%, or a range consisting of any two of these values, and P2 can be 0.05%, 0.08%, 0.1%, 0.5%, 0.8%, 1.1%, 1.5%, 2%, 3%, 5%, or a range consisting of any two of these values.
[0019] This application uses the first additive and the second additive together. Through the synergistic effect of the two, the degree of electrolyte infiltration under lean conditions can be improved, thereby improving the fast charging performance, cycle performance and high temperature resistance of lithium-ion batteries. Among them, the first additive can be preferentially reduced on the surface of the negative electrode during the battery charging and discharging process to form a dense, uniform, and highly ionic conductive SEI film (Solid electrolyte Interface), thereby effectively isolating the damage of the transition metal ions in the electrolyte to the negative electrode, reducing the impedance of the lithium-ion battery, and making the desolvation and charge transfer of lithium ions easier to occur, thereby improving the cycle stability and high temperature storage performance of the lithium-ion battery. However, the first additive will increase the viscosity of the electrolyte, thereby reducing the mobility of lithium ions in the electrolyte under lean conditions.
[0020] The substituents in the second additive form strong covalent bonds with the carbon atoms on the benzene ring, which makes it difficult to lose electrons in the electrochemical reaction. On the other hand, the structure of the substituted benzene ring becomes asymmetric, which makes the charge distribution in the molecule uneven, and the polarity of the molecule increases, which helps to improve the wettability of the electrolyte. In addition, from the perspective of molecular simulation, the second additive easily enters the first solvation layer of lithium ions, and the strong polarity makes it easier to form hydrogen bonds or other polar effects with the solvent molecules in the electrolyte, expand the first solvation radius, and reduce the concentration of free solvent molecules and additive molecules, thereby reducing the side reactions of the electrolyte on the electrode surface; further, because the substituents in the second additive can form hydrogen bonds with the first additive, the first additive enters the first solvation layer of lithium ions more quickly and is more easily reduced on the negative electrode surface, thereby producing a uniform and dense SEI film, while improving the first additive's obstruction to lithium ion migration, improving the mobility of lithium ions in the electrolyte, improving the fast charging performance of lithium ion batteries under lean conditions, and improving the battery's cycle performance and high temperature performance.
[0021] In addition, the homo (highest occupied molecular orbital) energy levels of the first additive and the second additive are higher than those of other components of the electrolyte, and they are preferentially decomposed at the positive electrode. The decomposition products enter the CEI membrane, which can improve the stability of the membrane and the cycle stability of the lithium-ion battery.
[0022] When the mass percentage P1 of the first additive is too small, for example, less than 0.1%, the SEI film formed has low strength, is easy to rupture when the negative electrode volume expands, is easily destroyed by transition metal ions in the electrolyte, and has poor ion conductivity, thereby increasing the impedance of the lithium-ion battery, thereby affecting the cycle stability and high-temperature storage performance of the lithium-ion battery; when the mass percentage P1 of the first additive is too large, for example, greater than 10%, it will cause the viscosity of the electrolyte to be too large, thereby affecting the mobility of lithium ions in the electrolyte under lean conditions. When the mass percentage P2 of the second additive is too small, for example, less than 0.05%, it is not conducive to the migration of lithium ions in the electrolyte, affects the degree of electrolyte infiltration, and thereby reduces the fast charging performance of lithium ions under lean conditions; when the mass percentage P2 of the second additive is too large, for example, greater than 5%, it will cause the SEI film to be too thick, and the capacity loss of the lithium-ion battery will be obvious. The electrolyte of the present application includes both the first additive and the second additive, and the contents of the first additive and the second additive are controlled within the scope of the present application. The synergistic effect of the two can improve the mobility of lithium ions in the electrolyte under lean conditions, thereby improving the fast charging performance, cycle performance and high temperature resistance of the lithium-ion battery.
[0023] Filling factor of lithium-ion battery = , in g / Ah, is usually determined by factors such as the battery shape (e.g. soft-pack, square, cylindrical) and the type of positive electrode active material (e.g. lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate). Taking soft-pack lithium iron phosphate batteries as an example, under normal circumstances, the filling coefficient of soft-pack lithium iron phosphate batteries is 3.5-4.5g / Ah. If the filling coefficient is lower than 3.5g / Ah, it can be regarded as a lean liquid condition, and the lithium-ion battery system corresponding to the lean liquid condition is a lean liquid system. In this application, a soft-pack lithium iron phosphate battery with a filling coefficient lower than 3.5g / Ah can be regarded as a lean liquid condition.
[0024] In some embodiments of the present application, the first additive is selected from at least one of the compounds represented by Formula 1-1 to Formula 1-4: .
[0025] In some embodiments of the present application, the second additive is selected from at least one of the compounds represented by Formula 2-1 to Formula 2-13: .
[0026] The present application uses the first additive and the second additive in combination, and through the synergistic effect of the two, the electrolyte infiltration degree of the lithium-ion battery under lean liquid conditions can be improved, thereby improving the fast charging performance, cycle performance and high temperature resistance of the lithium-ion battery.
[0027] In some embodiments of the present application, the additive includes a third additive, and the third additive is selected from at least one of vinylene carbonate, fluoroethylene carbonate, ethylene sulfate, 1,3-propane sultone, vinyl sulfite and difluorobis(oxalate)phosphate lithium; based on the total mass of the electrolyte, the mass percentage of the third additive is P3, 0.5%≤P3≤5%, preferably 1%≤P3≤2%. For example, P3 can be 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.1%, 2.3%, 2.5%, 2.7%, 2.9%, 3%, 3.5%, 4%, 5% or a range consisting of any two of the values. By adding the third additive to the electrolyte and controlling the mass percentage of the third additive within the scope of the present application, the uniformity of SEI film formation can be improved, and the fast charging performance, cycle performance and high temperature resistance of lithium ions under lean conditions can be further improved.
[0028] In some embodiments of the present application, the third additive is selected from vinylene carbonate and 1,3-propane sultone; the mass ratio of vinylene carbonate and 1,3-propane sultone is (0.25~4):1. For example, the mass ratio of vinylene carbonate and 1,3-propane sultone is 0.25:1, 0.5:1, 1:1, 1.5:1, 2:1, 3:1, 4:1 or a range consisting of any two of the values. Controlling the ratio of VC and PS within the above range can further improve the uniformity of SEI film formation and improve the fast charging performance, cycle performance and high temperature resistance of lithium ions under lean conditions.
[0029] The second aspect of the present application provides a lithium ion battery, which includes a positive electrode plate, a negative electrode plate, a separator and the electrolyte provided by the first aspect of the present application, wherein the positive electrode plate includes a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode material layer includes a positive electrode active material; based on the total mass of the positive electrode material layer, the mass percentage of the positive electrode active material is C p , the filling coefficient of lithium-ion battery is I c g / Ah, lithium-ion batteries meet: , preferably .For example, It can be 0.29, 0.5, 1, 2, 3, 4, 5, 10, 15, 20, 23.33, 27, 30, 40, 45, 50, 80, 100, 130, 148.75 or a range consisting of any two of these values. In this application, the mass percentage of the positive electrode active material Cp and the electrolyte injection coefficient I c It will directly affect the adequacy of the contact between the first additive and the second additive and the surface of the positive and negative electrode material layer, as well as the consumption, decomposition and diffusion rates of the first additive and the second additive on the surface of the positive and negative electrode material layer during the conversion stage. p ,I c , P1 and P2 are associated, and Controlling within the scope of the present application can reduce the viscosity of the electrolyte and improve the electrolyte infiltration degree of the lithium-ion battery under lean conditions; at the same time, it is beneficial for the first additive and the second additive to fully form a film on the surface of the electrode, reduce the impedance of the lithium-ion battery, and thus improve the fast charging performance, cycle performance and high temperature resistance of the lithium-ion battery.
[0030] In some embodiments of the present application, 2.2≤I c ≤3.5, 92%≤C p ≤98%, preferably 2.7≤I c ≤3, 94%≤C p ≤97%. For example, I c It can be 2.2, 2.4, 2.6, 2.7, 2.8, 2.9, 3, 3.2, 3.4, 3.5 or a range consisting of any two of them. p It can be 92%, 93%, 94%, 95%, 96%, 97%, 98% or a range consisting of any two of these values.
[0031] I c It is an important parameter that affects the relative quality of the positive and negative electrode material layers and the non-aqueous electrolyte in lithium-ion batteries. c Within the scope of the present application, the positive electrode sheet, negative electrode sheet and separator in the lithium-ion battery can be fully infiltrated with the electrolyte, and the first additive and the second additive can form a stable interface film on the surface of the positive electrode sheet and the negative electrode sheet, which is beneficial to fully utilize the capacity of the lithium-ion battery, thereby improving the fast charging cycle stability and high-temperature storage performance of the lithium-ion battery under lean conditions.
[0032] C p It will affect the electrolyte's wetting effect on the positive electrode and the volume expansion rate of the positive electrode, thus directly affecting the film formation and charge-discharge stability of the interface film. p Controlled within the scope of this application, the lithium-ion battery can have both high theoretical capacity and theoretical specific capacity and low production cost, while improving the degree of electrolyte infiltration into the electrode under lean conditions, promoting the film formation of the first additive and the second additive on the surface of the positive electrode material, enhancing the stability of the positive electrode structure and improving the fast charging performance and cycle stability of the lithium-ion battery. c and C pBy controlling within the scope of the present application, the electrolyte infiltration degree under lean liquid conditions can be further improved, and the fast charging performance, cycle performance and high temperature resistance of the lithium-ion battery can be improved.
[0033] In the present application, the electrolyte includes a non-aqueous organic solvent. As the main component of the electrolyte, the non-aqueous organic solvent should have a high solubility of lithium salt so that the electrolyte has a high ionic conductivity. As an important carrier for ion transmission, the non-aqueous organic solvent can have a high electronic conductivity when the lithium salt is dissolved, improving the cycle life, charge and discharge rate, high temperature performance, low temperature performance and energy density of the battery. The present application has no special restrictions on non-aqueous organic solvents, as long as the purpose of the present application can be achieved. For example, the non-aqueous organic solvent may include but is not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds or other organic solvents. The above-mentioned carbonate compounds may include but are not limited to at least one of chain carbonate compounds or cyclic carbonate compounds. The above-mentioned chain carbonate compounds may include but are not limited to at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate or methyl ethyl carbonate. The above-mentioned cyclic carbonate may include but is not limited to at least one of ethylene carbonate, propylene carbonate or butylene carbonate. The above-mentioned carboxylate compounds may include but are not limited to at least one of methyl formate, ethyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanolactone, valerolactone or caprolactone. The above-mentioned ether compounds may include but are not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate. The present application does not particularly limit the content of the non-aqueous organic solvent in the electrolyte, as long as the purpose of the present application can be achieved. For example, based on the total mass of the electrolyte, the mass percentage of the non-aqueous organic solvent may be 62% to 91%.
[0034] In the present application, the electrolyte includes a lithium salt. After the lithium salt is dissolved in the solvent of the electrolyte, lithium ions can be released, and the lithium ions and the solvent form a solvation structure, which is conducive to the rapid migration of lithium ions. The present application has no special restrictions on lithium salts, as long as the purpose of the present application can be achieved. For example, the lithium salt may include but is not limited to at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, Li2SiF6, LiFSI, lithium bis(oxalatoborate) (LiBOB), lithium bis(trifluoromethanesulfonylimide) (LiTFSI) or lithium difluoroborate. The present application has no special restrictions on the content of lithium salt in the electrolyte, as long as the purpose of the present application can be achieved.
[0035] In some embodiments of the present application, the lithium salt may include LiPF6 and LiFSI. Adding LiPF6 and LiFSI to the electrolyte at the same time can further reduce the gas production of the battery and improve the cycle performance of the battery.
[0036] In some embodiments of the present application, the mass ratio of LiPF6 to LiFSI is (2-5):1. For example, the mass ratio of LiPF6 to LiFSI is 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, or a range consisting of any two of these values. Controlling the ratio of LiPF6 to LiFSI within the above range can make the lithium-ion battery have excellent cycle performance and high-temperature storage performance, and can take into account the preparation cost of the battery, reduce gas production, and improve the cycle performance of the battery.
[0037] In some embodiments of the present application, the mass percentage of the lithium salt is 8% to 18%, preferably 10% to 16%, based on the total mass of the electrolyte. For example, based on the total mass of the electrolyte, the mass percentage of the lithium salt can be 8%, 10%, 12%, 14%, 16%, 18%, or a range consisting of any two of these values. Controlling the mass percentage of the lithium salt within the scope of the present application can make the lithium salt fully soluble in the non-aqueous organic solvent, while the electrolyte has both high ionic conductivity and low manufacturing cost.
[0038] The lithium-ion battery of the present application also includes a positive electrode plate, which includes a positive electrode collector and a positive electrode material layer disposed on at least one surface of the positive electrode collector. In the present application, the positive electrode material layer can be disposed on one surface in the thickness direction of the positive electrode collector, or on two surfaces in the thickness direction of the positive electrode collector. The present application has no particular restrictions on the positive electrode collector, as long as the purpose of the present application can be achieved. For example, the positive electrode collector may include a metal foil or a composite current collector, etc. For example, the metal foil is an aluminum foil. The composite current collector may include a polymer material base layer and a metal material layer located on at least one surface of the polymer material base layer. For example, the material of the metal material layer may include at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver or silver alloy. The polymer material base layer may include at least one of polypropylene, polyethylene terephthalate, polybutylene terephthalate, polystyrene or polyethylene. The present application has no particular restrictions on the thickness of the positive electrode collector and the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the positive electrode current collector is 5μm to 20μm, preferably 6μm to 18μm. The thickness of the single-sided positive electrode material layer is 30μm to 120μm. The positive electrode material layer of the present application may also include a conductive agent and a binder. The present application has no special restrictions on the conductive agent and the binder, as long as the purpose of the present application can be achieved. For example, the conductive agent may include but is not limited to at least one of superconducting carbon (Super P), acetylene black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. The binder may include but is not limited to polyvinyl chloride, polypropylene alcohol, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer or fluorine-containing acrylate resin.
[0039] In some embodiments of the present application, the positive electrode active material may be a positive electrode active material for lithium ion batteries known in the art. For example, the positive electrode active material includes but is not limited to lithium iron phosphate materials, LiCoO2 materials, lithium-rich manganese-based materials (aLi2MnO3•(1-a)LiMO2) (0≤a≤1) (M is Ni, Co, Mn), LiNi x Co y Mn z O2 (x+y+z=1) materials, lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O4) materials, lithium iron manganese phosphate (LiFe b Mn 1-b PO4) (0≤b≤1), etc.
[0040] The lithium-ion battery of the present application includes a negative electrode plate, which includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector. In the present application, the negative electrode material layer can be disposed on one surface in the thickness direction of the negative electrode current collector, or on two surfaces in the thickness direction of the negative electrode current collector. The present application has no particular restrictions on the negative electrode current collector, and any negative electrode current collector known in the art can be used as long as the purpose of the present application can be achieved. The negative electrode current collector can be a metal foil or a composite current collector. For example, as a metal foil, it can include at least one of aluminum foil, copper foil, nickel foil, and titanium foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of a polymer material substrate. The composite current collector can be formed by compounding a metal material (copper, copper alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), etc.).
[0041] In the present application, there is no particular restriction on the thickness of the negative electrode current collector and the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode current collector is 4μm to 15μm, and the thickness of the single-sided negative electrode material layer is 30μm to 150μm. Optionally, the negative electrode active material includes a thickener, and the thickener may include but is not limited to sodium carboxymethyl cellulose (CMC-Na). The negative electrode material layer of the present application may also include a conductive agent and a binder. The present application has no particular restrictions on the conductive agent and the binder, as long as the purpose of the present application can be achieved. For example, the binder may include at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS). The conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0042] The negative electrode material layer of the present application contains negative electrode active materials. The present application does not particularly limit the type of negative electrode active materials, and any negative electrode active materials known in the art can be used as long as the purpose of the present application can be achieved. For example, the negative electrode active material may include at least one of artificial graphite, natural graphite, soft carbon, hard carbon, mesophase carbon microspheres, silicon-based materials, tin-based materials and lithium titanate. The above-mentioned silicon-based materials may include but are not limited to at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites or silicon alloys; the above-mentioned tin-based materials may include at least one of elemental tin, tin oxide compounds or tin alloys.
[0043] The lithium-ion battery of the present application also includes a diaphragm to separate the positive electrode plate and the negative electrode plate, prevent the internal short circuit of the battery, allow ions to pass freely, and do not affect the electrochemical charge and discharge process. The present application has no particular restrictions on the type of diaphragm, and any porous structure diaphragm with good chemical stability and mechanical stability can be selected. For example, the material of the diaphragm may include at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The type of diaphragm may include but is not limited to at least one of woven membrane, non-woven membrane (non-woven fabric), microporous membrane, composite membrane, rolled membrane or spinning membrane. The diaphragm can be a single-layer film or a multi-layer composite film. In the present application, the thickness of the diaphragm is not particularly limited, as long as the purpose of the present application can be achieved, for example, the thickness can be 10μm to 25μm.
[0044] The lithium-ion battery of the present application also includes a packaging bag for containing a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, as well as other components known in the art, and the present application does not limit the above-mentioned other components. The present application does not specifically limit the packaging bag, and it can be a packaging bag known in the art, as long as it can achieve the purpose of the present application. For example, an aluminum-plastic film packaging bag can be used.
[0045] The preparation process of the lithium-ion battery of the present application is well known to those skilled in the art, and the present application has no particular limitation. For example, it may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding and folding them as needed to obtain an electrode assembly of a winding structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain a lithium-ion battery; or stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and then fixing the four corners of the entire stacked structure with tape to obtain an electrode assembly of a stacked structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain a lithium-ion battery. In addition, overcurrent protection components, guide plates, etc. may also be placed in the packaging bag as needed to prevent the pressure inside the lithium-ion battery from rising and overcharging and discharging.
[0046] The battery of the present application may include a battery cell form, a battery module form and a battery pack form. Battery cells can be assembled into a battery module, and the number of battery cells contained in the battery module can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery module. The battery module of the present application can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery pack.
[0047] Example Hereinafter, the embodiments of the present application will be described in more detail with reference to Examples and Comparative Examples. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are by mass.
[0048] Test methods and equipment: High temperature storage performance test Place the lithium-ion battery in a constant temperature environment at 25°C, charge it at a constant current of 1C to a voltage of 3.65V, charge it at a constant voltage at 3.65V to a cut-off current of 0.05C, and then discharge it at a constant current of 1C to 2V. The first discharge capacity is recorded as the capacity before storage, recorded as C0. Charge it again at a constant current of 1C to a voltage of 3.65V, charge it at a constant voltage at 3.65V to a cut-off current of 0.05C, place the lithium-ion battery in an explosion-proof oven at 60°C for 30 days, and then discharge it at a constant current of 1C to 2V. This is the capacity after storage, recorded as C m . High temperature storage capacity retention rate = (C m / C0)×100%.
[0049] Fast charging performance test Place the lithium-ion battery in a constant temperature environment at 25°C, charge it at a constant current of 4C to a voltage of 3.65V, charge it at a constant voltage of 3.65V to a cut-off current of 0.05C, and then discharge it at a constant current of 1C to 2V. Repeat the above charge and discharge three times, and record the maximum discharge capacity of the first three times as Q. Then repeat the above charge and discharge cycle process to 2000 weeks, and record the discharge capacity of the 2000th week as Q1.
[0050] High temperature cycle capacity retention rate = Q1 / Q×100%.
[0051] Example 1-1 <Preparation of Electrolyte> In an inert atmosphere with water content less than 0.1ppm and oxygen content less than 0.1ppm, ethylene carbonate (EC) and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 30:70 to obtain a base solvent. Lithium salts (LiPF6 and LiFSI), compounds of formula 1-1, and compounds of formula 2-1 are added to the base solvent and mixed evenly to obtain an electrolyte. Based on the total mass of the electrolyte, the mass percentage of the compound of formula 1-1 is 0.1%, the mass percentage of the compound of formula 2-1 is 1.0%, the mass percentage of LiFSI is 3%, the mass percentage of LiPF6 is 9%, and the rest is the base solvent.
[0052] <Preparation of positive electrode sheet> The positive electrode active material lithium iron phosphate (LiFePO4), the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 96:2:2, and N-methylpyrrolidone (NMP) is added. The mixture is stirred evenly under the action of a vacuum mixer until the mixed system becomes a positive electrode slurry with uniform fluidity, and a positive electrode slurry with a solid content of 60wt% is obtained. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 16μm, and dried at 80°C to obtain a positive electrode sheet coated with a positive electrode material layer on one side. Repeat the above steps on the other surface of the positive electrode current collector aluminum foil to obtain a positive electrode sheet coated with a positive electrode material layer on both sides. After drying under vacuum conditions at 80°C, a positive electrode sheet with a specification of 70mm×54mm is obtained through processes such as cold pressing, trimming, cutting, striping, sheeting, and welding of the pole ear glue. Among them, the compaction density of the positive electrode material layer is 2.4g / cm 3 .
[0053] <Preparation of negative electrode sheet> The negative electrode active material artificial graphite, conductive agent conductive carbon black (SuperP), thickener sodium carboxymethyl cellulose (CMC) and adhesive styrene butadiene rubber (SBR) are mixed in a mass ratio of 94.5:2:1.5:2, deionized water is added, and the mixture is stirred evenly under the action of a vacuum mixer to obtain a negative electrode slurry with a solid content of 50wt%. The negative electrode slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 9μm, and after drying at 80°C, a negative electrode sheet with a single-sided coating of a negative electrode material layer with a coating thickness of 100μm is obtained. Repeat the above steps on the other surface of the negative electrode current collector copper foil to obtain a negative electrode sheet with a double-sided coating of a negative electrode material layer. After drying under vacuum conditions at 80°C, a negative electrode sheet with a specification of 74mm×58mm is obtained through processes such as cold pressing, trimming, cutting, striping, sheeting and welding of the pole ear glue. Among them, the compaction density of the negative electrode material layer is 1.6g / cm 3 .
[0054] <Preparation of Separator> The diaphragm is a polypropylene (PP) diaphragm purchased from Dongguan Kelude, with a thickness of 16 μm.
[0055] <Preparation of lithium-ion batteries> The separator, positive electrode sheet, separator and negative electrode sheet are stacked in order, so that the separator is between the positive electrode sheet and the negative electrode sheet, the positive electrode sheet and the negative electrode sheet are isolated, and then wound, the positive electrode ear is connected to the positive electrode sheet, and the negative electrode ear is connected to the negative electrode sheet, so as to obtain an electrode assembly. The electrode assembly is put into an aluminum foil packaging bag, and the positive and negative electrode ears are led out from the inner space of the packaging bag to the outer space of the packaging bag, and after drying at 85°C for 36 hours to remove moisture, hot pressing and sealing are performed to obtain a battery cell to be injected with liquid. Then the prepared electrolyte is injected into the dried battery cell, and after vacuum packaging, standing, formation, shaping, capacity division and other processes, a lithium-ion battery is obtained.
[0056] Example 1-2 to Example 1-10 The same as Example 1-1 except that the mass percentage content P1 of the first additive is adjusted according to Table 1. When the value of P1 in the electrolyte changes, the mass percentage content of the base solvent changes accordingly, and the mass percentage content of the electrolyte remains unchanged.
[0057] Example 1-11 to Example 1-17 Except for adjusting the mass percentage content P2 of the second additive according to Table 1, the rest is the same as Example 1-4. When the value of P2 in the electrolyte changes, the mass percentage content of the base solvent changes accordingly, and the mass percentage content of the electrolyte remains unchanged.
[0058] Example 1-18 to Example 1-26 In addition to adjusting I c Other than that, the rest is the same as Example 1-4.
[0059] Example 1-27 to Example 1-34 In addition to adjusting C according to Table 1 p Except for this, the rest is the same as that of Example 1-4. p When the value of changes, the conductive agent and the binder in the positive electrode material layer increase or decrease in a 1:1 ratio.
[0060] Example 1-35 to Example 1-37 In addition to adjusting P1, P2, I c and C p Except for the above, the rest is the same as that of Example 1-4. When the values of P1 and P2 in the electrolyte change, the mass percentage of the base solvent changes accordingly, and the mass percentage of the electrolyte remains unchanged; C p When the value of changes, the conductive agent and the binder in the positive electrode material layer increase or decrease in a 1:1 ratio.
[0061] Example 2-1 to Example 2-12 Except for adjusting the types of the first additive and the second additive according to Table 2, the rest is the same as Example 1-4.
[0062] Example 3-1 to Example 3-7 The other aspects are the same as those of Example 1-4 except that the third additive is added to the electrolyte according to Table 3. After the third additive is added, the mass percentage of the base solvent changes accordingly, while the mass percentage of the electrolyte remains unchanged.
[0063] Comparative Example 1 to Comparative Example 2 Except that only the first additive or the second additive is added in <Preparation of the electrolyte>, and the content of the first additive or the second additive is adjusted according to Table 1, the rest is the same as Example 1-4. When the value of P1 or P2 in the electrolyte changes, the mass percentage of the base solvent changes accordingly, and the mass percentage of the electrolyte remains unchanged.
[0064] Comparative Examples 3 to 6 Except for adjusting the contents of the first additive and the second additive in <Preparation of Electrolyte> according to Table 1, the rest is the same as Example 1-4. When the values of P1 and P2 in the electrolyte change, the mass percentage of the base solvent changes accordingly, and the mass percentage of the electrolyte remains unchanged.
[0065] The preparation parameters and performance parameters of each embodiment and comparative example are shown in Tables 1 to 3.
[0066] Table 1
[0067] Note: “ / ” in Table 1 means no relevant parameters.
[0068] It can be seen from Examples 1-1 to 1-17 and Comparative Examples 1 to 6 that the electrolyte includes the first additive and the second additive, and the contents of the first additive and the second additive are adjusted within the scope of the present application, so that the lithium-ion battery can have a higher cycle capacity retention rate and storage capacity retention rate under lean conditions. The electrolytes of Comparative Examples 1 and 2 contain only one of the first additive or the second additive, the content of the first additive in Comparative Example 3 is too low, the content of the first additive in Comparative Example 4 is too high, the content of the second additive in Comparative Example 5 is too low, and the content of the second additive in Comparative Example 6 is too high, and the lithium-ion battery has a lower cycle capacity retention rate and a lower storage capacity retention rate under lean conditions. This indicates that if the electrolyte does not include the first additive and the second additive at the same time, or the contents of the first additive and the second additive are not within the scope of the present application, the cycle capacity retention rate and storage capacity retention rate of the lithium-ion battery under lean conditions are both poor.
[0069] I c It is an important parameter that affects the relative quality of the positive and negative electrode material layers and the non-aqueous electrolyte in lithium-ion batteries. It can be seen from Examples 1-19 to 1-25 of the present application that the regulation of I c The value of is within the scope of this application, which can make the lithium ion battery have a higher cycle capacity retention rate and storage capacity retention rate. c The value of is too low, and in Example 1-26, c The value of is too high, and its lithium-ion batteries have a lower cycle capacity retention rate and a lower storage capacity retention rate.
[0070] C p It will affect the wetting effect of the electrolyte on the positive electrode and the volume expansion rate of the positive electrode, thereby directly affecting the film formation and charge and discharge stability of the interface film. It can be seen from Examples 1-27 to 1-34 of the present application that the regulation of I c The value of is within the scope of the present application, which can enable the lithium-ion battery to have a higher cycle capacity retention rate and storage capacity retention rate under lean liquid conditions, indicating that the lithium-ion battery has better fast charging performance, cycle performance and high temperature resistance under lean liquid conditions.
[0071] It can be seen from Examples 1-1 to 1-37 that by p ,I c , P1 and P2 are associated, and Controlling within the scope of the present application can enable the lithium-ion battery to have a higher cycle capacity retention rate and storage capacity retention rate under lean liquid conditions, indicating that the lithium-ion battery has better fast charging performance, cycle performance and high temperature resistance under lean liquid conditions.
[0072] Table 2
[0073] The types of the first additive and the second additive usually affect the fast charging performance, cycle performance and high temperature resistance of the lithium-ion battery under lean liquid conditions. It can be seen from Examples 2-1 to 2-12 that the selection of the first additive and the second additive within the scope of the present application can enable the lithium-ion battery to have a higher cycle capacity retention rate and storage capacity retention rate under lean liquid conditions, indicating that the lithium-ion battery has better fast charging performance, cycle performance and high temperature resistance under lean liquid conditions.
[0074] Table 3
[0075] Note: “ / ” in Table 3 indicates no relevant parameters.
[0076] Further introducing a third additive into the electrolyte can improve the uniformity of SEI film formation and further improve the fast charging performance, cycle performance and high temperature resistance of the lithium-ion battery. It can be seen from Examples 3-1 to 3-7 and Examples 1-4 that adding a third additive to the electrolyte and controlling the content of the third additive within the scope of this application can further improve the cycle capacity retention rate and storage capacity retention rate of the lithium-ion battery under lean conditions, indicating that the lithium-ion battery has better fast charging performance, cycle performance and high temperature resistance under lean conditions.
[0077] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. An electrolyte comprising a non-aqueous organic solvent, a lithium salt and an additive; the additive comprising a first additive and a second additive, the first additive comprising a compound represented by Formula 1, and the second additive comprising a compound represented by Formula 2: ; in, R1 and R2 are each independently selected from hydrogen, unsubstituted or a Replaced , unsubstituted or replaced by R a Replaced , unsubstituted or replaced by R a Replaced , and R1 and R2 are not hydrogen at the same time; R a Selected from , or ; R3, R4 and R5 are each independently selected from carbon, oxygen, or , and at least one of R3, R4 and R5 is selected from or , at least one of R3, R4 and R5 is selected from oxygen atoms; and the compound represented by formula 1 contains at least one and a ; R6-R 11 are independently selected from hydrogen, halogen, phenyl, hydroxyl, C1-C6 hydrocarbon group, C1-C6 halogenated hydrocarbon group, and R6-R 11 Not at the same time hydrogen; Based on the total mass of the electrolyte, the mass percentage of the first additive is P1, the mass percentage of the second additive is P2, 0.1%≤P1≤10%, 0.05%≤P2≤5%.
2. The electrolyte according to claim 1, wherein 0.25%≤P1≤2%, 0.1%≤P2≤1.5%.
3. The electrolyte according to claim 1, wherein The first additive is selected from at least one of the compounds represented by Formula 1-1 to Formula 1-4: 。 4. The electrolyte according to claim 1, wherein The second additive is selected from at least one of the compounds represented by Formula 2-1 to Formula 2-13: 。 5. The electrolyte according to any one of claims 1 to 4, wherein The additives include a third additive, and the third additive is selected from at least one of vinylene carbonate, fluoroethylene carbonate, ethylene sulfate, 1,3-propane sultone, vinyl sulfite and lithium difluorobis(oxalate)phosphate; based on the total mass of the electrolyte, the mass percentage of the third additive is P3, 0.5%≤P3≤5%, preferably, 1%≤P3≤2%.
6. The electrolyte according to claim 5, wherein The third additive is selected from vinylene carbonate and 1,3-propane sultone; the mass ratio of vinylene carbonate to 1,3-propane sultone is (0.25~4):
1.
7. A lithium ion battery comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte according to any one of claims 1 to 6, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode material layer comprises a positive electrode active material; based on the total mass of the positive electrode material layer, the mass percentage of the positive electrode active material is C p The injection coefficient of the lithium ion battery is I c g / Ah, the lithium-ion battery meets the following requirements: .
8. The lithium ion battery according to claim 7, wherein: 2.2≤I c ≤3.5,92%≤C p ≤98%。 9. The lithium ion battery according to claim 7, wherein: 。 10. The lithium ion battery according to claim 7, wherein: 2.7≤I c ≤3,94%≤C p ≤97%。
Citation Information
Patent Citations
Lithium ion battery
CN114068936A
Lithium ion battery
CN114695944A
Non-aqueous electrolyte and lithium ion battery
CN116190788A
Lithium ion battery
CN116404253A
Electrolyte and secondary battery
CN118630316A
Cited By
Electrolytic solution and lithium-ion battery
WO2026108894A1